1998
DOI: 10.1017/s0007485300042176
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of foliar and systemic applications of acetamiprid and imidacloprid against the cotton whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae)

Abstract: Comparative bioassays of two chloronicotinyl insecticides, acetamiprid and imidacloprid, against the whitefly Bemisia tabaci (Gennadius), using foliar and systemic applications, were conducted under laboratory conditions and in field trials. Under controlled conditions, the ovicidal activity of foliar applications of acetamiprid on cotton seedlings was much higher than that of imidacloprid. According to LC50 and LC90 values, acetamiprid was 10- and 18-fold more potent than imidacloprid. Both compounds were eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 17 publications
(20 reference statements)
6
45
0
1
Order By: Relevance
“…The treatments were compared with each other using one way ANOVA with LSD 0.05 (CoStat Statistical Software, 1990 (2012 and 2013). The same gradual increasing in reduction percentages in whitefly numbers was recorded with the nicotinic acetylcholine receptor agonist Confidor (imidacloprid), which was potent on days 7 and 14 after application as recorded by Motohiro and Casida (2003); Horowitz et al (1998). Our results were comparable with El Bessomy (2003), where he reported that Admire (imidacloprid) gave good reduction percentages against the whitefly after 84 hrs of application.…”
Section: Materials and Methods Tested Insecticides And Control Agentssupporting
confidence: 89%
“…The treatments were compared with each other using one way ANOVA with LSD 0.05 (CoStat Statistical Software, 1990 (2012 and 2013). The same gradual increasing in reduction percentages in whitefly numbers was recorded with the nicotinic acetylcholine receptor agonist Confidor (imidacloprid), which was potent on days 7 and 14 after application as recorded by Motohiro and Casida (2003); Horowitz et al (1998). Our results were comparable with El Bessomy (2003), where he reported that Admire (imidacloprid) gave good reduction percentages against the whitefly after 84 hrs of application.…”
Section: Materials and Methods Tested Insecticides And Control Agentssupporting
confidence: 89%
“…However, the alleged efficiency of imidacloprid against a broad range of insect-pests, such as defoliators, thrips, and whiteflies (Orozco et al 1995, Elbert et al 1998, was not observed in our investigation, probably due to the environmental conditions of our experiment, which was carried out in a tropical area during the rainy season. Despite this particularity, imidacloprid was shown not to affect whiteflies and the thrips Frankliniella sp (Zhao et al 1995, Horowitz et al 1998). In our study we observed significant effect of imidacloprid on two thrips, T. tabaci and C. brasiliensis, but not on Frakliniella sp., that is curious and deserves further attention.…”
Section: E Kraemeri/100mentioning
confidence: 95%
“…Further, the larvicidal effect of the insecticide was clearly dependent on the concentrations of the insecticide. Bhatnagar et al [8] also reported that the relative toxicity ratio ( [9] reported that according to LC 50 and LC 90 values, acetamiprid was 10-and 18-folds more potent than imidacloprid to whitefly Bemisia tabaci (Gennadius) resulting (with the concentration of 25 ml a.i./l) in adult mortality of 90, 93, and 96% and 76, 84 and 76% after 2, 7 and 14 days of application. Acetamiprid, (E) -N 1-[(6 -chloro -3-pyridyl) methyl] -N 2-cyano-N1-methyl acetamidile, is a new-generation novel insecticide with ground and aerial application.…”
Section: Integrated Management Options-no Doubtmentioning
confidence: 99%